A cobalt-based amorphous soft magnetic material, a constant magnetic permeability magnetic core, and a preparation method and application thereof

By adjusting the element content and preparation process in the cobalt-based amorphous soft magnetic material, a cobalt-based amorphous constant permeability magnetic core with high magnetic permeability, saturated magnetic field strength and low loss was prepared, solving the problems of insufficient performance of existing magnetic cores and complex preparation, and achieving efficient and economical core production.

CN117995504BActive Publication Date: 2025-03-07BEIJING SHOU YE MAGNETIC MATERIAL SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410121009.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-03-07
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

The existing high-precision current transformer cores cannot meet the requirements of high saturation magnetic field strength, low loss, low coercivity and good DC resistance. The preparation process is complex and costly, making it difficult to apply in large-scale batches.

Method used

Cobalt-based amorphous soft magnetic material was used to adjust the contents of Fe, Mn, Mo, Si, and B to prepare a cobalt-based amorphous constant permeability with a magnetic permeability of 2800~3500, high saturation magnetic field strength, low loss and low coercive force, and spray the amorphous tape by a single-roll melt fast quenching method, followed by magnetic field heat treatment to improve the core performance.

Benefits of technology

It realizes the high saturation magnetic field strength, low loss, low coercivity and good DC resistance of the cobalt-based amorphous constant conduction magnetic core, meets the requirements of the use of high-precision current transformers, simplifies the preparation process, reduces production costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117995504B_ABST
    Figure CN117995504B_ABST
Patent Text Reader

Abstract

The present application relates to a cobalt-based amorphous soft magnetic material, a constant magnetic permeability core, and a preparation method and application in the field of new material soft magnetic alloys. In terms of atomic percentage, the soft magnetic material is composed of the following elements: Fe: 0.5~5%, Mn: 1~6%, Mo: 3~6%, Si: 10~20%, B: 5~20%, Co: balance; and the sum of the atomic percentage content of Mn and Mo is 4~8%. The present application controls the content of Co, Fe, Mn, Mo, Si and B elements within a specific range, so that the cobalt-based amorphous constant magnetic permeability core prepared using the cobalt-based amorphous soft magnetic material as a master alloy has different constant magnetic fields, and the magnetic permeability is 2800~3500. At the same time, the cobalt-based amorphous constant magnetic permeability core also has high saturation magnetic field intensity Bs, low loss, low coercive force, and especially has good frequency characteristics and bias characteristics, meeting the use requirements of high-precision current transformers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new material soft magnetic alloys, and in particular to a cobalt-based amorphous soft magnetic material, a constant magnetic permeability magnetic core, and a preparation method and application thereof. Background Art

[0002] Smart grid is built on the basis of integrated, high-speed two-way communication network. Through the application of advanced sensing and measurement technology, advanced equipment technology, advanced control methods and advanced decision support system technology, it realizes the goal of reliable, safe, economical, efficient, environmentally friendly and safe use of power grid. Smart grid is composed of many parts, which can be divided into: smart substation, smart distribution network, smart energy meter, smart interactive terminal, smart dispatching, smart home appliances, smart electricity buildings, smart city electricity, etc. Among them, the "route" of power data transmission - power communication technology is a crucial part of smart grid construction. Power carrier communication (PLC) is the dominant mode of power communication now.

[0003] The core component of the smart meter is the high-precision current transformer used for measurement. With the promotion and use of the new standard for DC-resistant energy meters, the traditional current transformer core can no longer meet the requirements for DC-resistant components. It is necessary to develop magnetic materials and cores with certain DC-resistant capabilities, high saturation magnetic field strength Bs, and high constant magnetic permeability. At the same time, such materials and cores can also be widely used in power carrier communications (PLC), which have great economic and social benefits.

[0004] The core component of the new meter is the high-precision current transformer, which plays a key role in high-precision measurement. At present, the precision current transformer mainly changes the magnetic parameters of the current transformer core to meet the DC component requirements and avoid magnetic saturation. The magnetic cores currently produced by the industry include: composite cores, nanocrystalline cores and amorphous cores. Nanocrystalline cores ensure that the core has high magnetic permeability, low ratio difference and angle difference; while amorphous cores have high saturation magnetic field intensity Bs and low magnetic permeability, which can meet higher DC bias requirements; composite cores have unstable errors and are currently mainly used in some work situations with low precision requirements and relatively stable alternating frequencies, and cannot meet the performance requirements of high-precision current transformers.

[0005] The main research direction of high-precision current transformers is to achieve higher DC bias through a single magnetic core. This type of magnetic core has low and constant magnetic permeability, small attenuation with increasing magnetic field strength, good DC resistance, and high saturation magnetic induction. The angular difference and ratio difference of the transformer are approximately constants, and their errors can be calibrated through a simple compensation circuit.

[0006] At present, the main preparation methods for high-linearity and low-permeability magnetic cores are: (1) tension annealing treatment. After annealing, the nanocrystals have low constant magnetic permeability characteristics, but because the alloy is processed in a single strip and is prone to brittle fracture, the processing efficiency is low and the production cost is high, making it difficult to apply it on a large scale; (2) adjusting the alloy composition. Currently, it is mainly iron-based nanocrystalline alloys. The transverse magnetic field treatment temperature is high and the insulation time is long. The transverse magnetic field strength is too large and the processing process is complicated.

[0007] Therefore, it is very necessary to develop a magnetic core suitable for high-precision current transformers with high saturation induction, low coercive force, good DC resistance, constant magnetic permeability and good stability. Summary of the invention

[0008] In order to address the deficiencies in the prior art, the present application provides a cobalt-based amorphous soft magnetic material. Through the combination of various elements, the cobalt-based amorphous soft magnetic material makes the magnetic permeability of the cobalt-based amorphous constant magnetic permeability magnetic core prepared using the soft magnetic material reach 2800~3500, and at the same time has high saturation magnetic field intensity Bs, low loss, low coercive force, and especially has good frequency characteristics and bias characteristics.

[0009] To this end, the first aspect of the present application provides a cobalt-based amorphous soft magnetic material, which is composed of the following elements in atomic percentage: Fe: 0.5~5%, Mn: 1~6%, Mo: 3~6%, Si: 10~20%, B: 5~20%, Co: balance; and the sum of the atomic percentage contents of Mn and Mo is 4~8%.

[0010] The soft magnetic material described in the present application is based on Co, and a small amount of Fe, Mn, Mo, Si and B are added. By introducing the Fe element, the magnetostriction coefficient λs of the constant magnetic core made of the soft magnetic material can be gradually changed from a negative value to a positive value, and when the iron content is appropriate (0.5~5%), λs=0, so that the constant magnetic core can obtain a higher initial magnetic permeability; by introducing Si and B elements, the amorphous forming ability and soft magnetic properties of the constant magnetic core can be improved. The amorphous forming ability of Si element is lower than that of B element, but the addition of Si element can improve the thermal stability of the constant magnetic core to a certain extent. By controlling the Si and B elements in the material to an appropriate range, which helps to make the comprehensive performance of the constant magnetic permeability core better; by introducing the Mn element, the range of λs=0 of the constant magnetic permeability core can be widened, the stability of the constant magnetic permeability core can be improved, and the saturation magnetic field strength and mechanical properties can be enhanced; the introduction of the Mo element can improve the frequency characteristics of the constant magnetic permeability core, and further improve the stability of the constant magnetic permeability core, and the introduction of the Mo element can also improve the mechanical properties of the constant magnetic permeability core; but the content of the Mn element and the Mo element cannot be too high, otherwise the coercive force of the constant magnetic permeability core will be increased, and the amorphous forming ability of the core will be affected.

[0011] In some specific embodiments, the sum of the atomic percentage contents of Mn and Mo can be, for example, 4%, 4.5%, 5.0%, 5.5%, 6.0%, 7.0%, 7.8% or 8.0%. In some preferred embodiments, the sum of the atomic percentage contents of Mn and Mo is 4.5% to 6.0%. The present application controls the sum of the contents of Mn and Mo elements in the material to be within the range of 4 to 8%, especially within the range of 4.5% to 6.0%, so that the constant permeability magnetic core has excellent soft magnetic properties and mechanical properties.

[0012] In some embodiments, the sum of the atomic percentage contents of Si and B is 16-28%, and the atomic percentage content ratio of Si to B is (1-2):1.

[0013] In some preferred embodiments, the sum of the atomic percentage contents of Si and B is 18-24%, and the atomic percentage content ratio of Si to B is (1.5-2):1.

[0014] The present application controls the sum of the contents of Si and B elements and their content ratio within the above ranges, so that the finally prepared constant permeability magnetic core can have more excellent amorphous forming ability and soft magnetic properties.

[0015] In some embodiments, the atomic percentage content of Fe is 3-3.5%.

[0016] In the present application, although the introduced Fe element can make the final constant magnetic permeability core have a higher initial magnetic permeability and saturation magnetic field strength Bs, excessive Fe content will make the coercive force of the constant magnetic permeability core too high, thereby causing high loss and excessive energy consumption. By optimizing the atomic percentage content of the Fe element, the constant magnetic permeability core can have better comprehensive performance.

[0017] The second aspect of the present application provides a cobalt-based amorphous constant magnetic permeability core, wherein the master alloy used in the preparation process of the constant magnetic permeability core is the soft magnetic material as described in the first aspect of the present application.

[0018] The characteristics of the cobalt-based amorphous soft magnetic material described in the present application are mainly obtained by adjusting the contents of Fe, Mn, Mo, Si, and B. Through the specific contents of Co, Fe, Mn, Mo, Si and B elements, the cobalt-based amorphous constant magnetic permeability core prepared using the cobalt-based amorphous soft magnetic material as the master alloy has different constant magnetic fields, and the magnetic permeability is 2800~3500. At the same time, the cobalt-based amorphous constant magnetic permeability core also has high saturation magnetic field intensity Bs, low loss, and low coercive force, especially has better frequency characteristics and bias characteristics, increases energy storage density, and thus improves the constancy of inductance.

[0019] The third aspect of the present application provides a method for preparing the cobalt-based amorphous constant magnetic permeability core as described in the second aspect of the present application, the method comprising the following steps:

[0020] S1, spraying the master alloy into an amorphous strip by a single-roll melt rapid quenching method, and then winding the amorphous strip into a magnetic core;

[0021] S2, performing magnetic field heat treatment on the magnetic core under inert gas protection or vacuum conditions to obtain a magnetic core after magnetic field heat treatment;

[0022] S3, cooling the magnetic core after the magnetic field heat treatment to room temperature to obtain the cobalt-based amorphous constant magnetic permeability magnetic core.

[0023] The cobalt-based amorphous constant magnetic permeability core described in the present application is prepared by using a melt rapid quenching method to make amorphous strips from a master alloy, then winding the strips into a magnetic core, and subjecting it to a magnetic field heat treatment. The bias field characteristics of the cobalt-based amorphous constant magnetic permeability core prepared using the method described in the present application can reach 0~213A / m, with a variation of <2%, and a coercive force Hc of <0.2A / m under direct current. At the same time, the method described in the present application does not include a special preparation process, and can be realized only under industrial conditions, is suitable for industrial production, and has high practicality.

[0024] In the present application, the master alloy, that is, the cobalt-based amorphous soft magnetic material in the present application, can be prepared by: converting the nominal components of the elements Co, Fe, Mn, Mo, Si and B in the cobalt-based amorphous soft magnetic material into weight percentages, weighing and mixing the ingredients, and then smelting them for multiple times (4 to 5 times) to obtain the master alloy.

[0025] In some embodiments, in step S1, the linear speed of the cooling roller during the preparation of the amorphous strip is 35-40 m / s, and the thickness of the prepared amorphous strip is 16-24 μm and the width is 5-30 mm.

[0026] In the present application, the amorphous strip is prepared by a single-roll melt quenching method, which can be carried out in a vacuum single-roll melt quenching device, and the distance between the nozzle and the cooling roller can be 1.5~2mm. During the preparation process, the master alloy is first heated and melted into a melt, and then the melt is directly sprayed from the nozzle to the surface of the high-speed rotating cooling roller. The cooling roller quickly cools the master alloy melt sprayed on its surface. Due to the extremely high cooling rate, the alloy has no time to crystallize and becomes an amorphous alloy, thereby obtaining an amorphous strip. During the preparation process, the linear speed of the cooling roller has a great influence on the thickness of the obtained amorphous strip. The thickness of the amorphous strip decreases with the increase of the linear speed of the cooling roller. In the present application, the linear speed of the cooling roller is controlled at 35~40m / s, so that the thickness of the obtained amorphous strip is 16~24μm. The thickness and width of the amorphous strip will also have a great influence on the soft magnetic properties of the finally prepared cobalt-based amorphous constant magnetic permeability core. The present application helps to further improve the saturation magnetic field strength of the constant magnetic permeability core by controlling the thickness and width of the strip within the above range.

[0027] In some specific embodiments, the thickness of the amorphous ribbon may be, for example, 16 μm, 18 μm, 20 μm, 22 μm or 24 μm, and the width of the amorphous ribbon may be, for example, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm or 30 mm.

[0028] In some embodiments, in step S2, the heating rate during the magnetic field heat treatment is 1-10°C / min, the holding temperature is 300-400°C, and the holding time is 0.5-5 hours.

[0029] In the present application, when the magnetic core is subjected to magnetic field heat treatment, it is necessary to gradually heat up to the required temperature, and the heating rate can be 1~10℃ / min. If the heating rate is too fast, it is easy to cause the local temperature of the magnetic core to be too high, affecting the soft magnetic properties of the obtained constant magnetic conductivity core. At the same time, the insulation temperature during the magnetic field heat treatment in the present application is below 400℃, and the insulation temperature is low to avoid inducing alloy crystallization during the magnetic field heat treatment, thereby destroying the formation of amorphous structure. By controlling the insulation temperature and time within the above range, the present application is conducive to making the obtained constant magnetic conductivity core have better saturation magnetic induction intensity and coercive force.

[0030] In some embodiments, the magnetic field intensity during the magnetic field heat treatment is 10-100 kA / m.

[0031] In some specific embodiments, the magnetic field intensity during the magnetic field heat treatment can be, for example, 10 kA / m, 30 kA / m, 50 kA / m, 80 kA / m or 100 kA / m, etc. In some preferred embodiments, the magnetic field intensity during the magnetic field heat treatment is 30-80 kA / m.

[0032] Similarly, when performing magnetic field heat treatment, the magnetic field strength will also affect the saturation magnetic induction intensity and coercive force of the constant magnetic permeability core obtained. By controlling the magnetic field strength within the above range, it helps to make the constant magnetic permeability core obtained have better saturation magnetic induction intensity and coercive force.

[0033] In some embodiments, in step S3, the cooling rate is 3-10°C / min. In some specific embodiments, the cooling rate can be, for example, 3°C / min, 5°C / min, 8°C / min or 10°C / min.

[0034] In the present application, when cooling the magnetic core after magnetic field heat treatment, it is necessary to control the cooling rate to avoid the generation of internal stress during the cooling process, which will affect the soft magnetic properties of the obtained constant magnetic permeability magnetic core.

[0035] In a fourth aspect, the present application provides an application of the cobalt-based amorphous constant magnetic permeability core as described in the second aspect of the present application or the cobalt-based amorphous constant magnetic permeability core prepared by the method described in the third aspect in the preparation of a high-precision current transformer.

[0036] In the present application, the magnetic permeability of the cobalt-based amorphous constant magnetic core is 2800~3500, and it also has high saturation magnetic field intensity Bs, low loss, and low coercive force, especially good frequency characteristics and bias characteristics, which increases the energy storage density and thus improves the constancy of inductance, meeting the use requirements of high-precision current transformers, and therefore can be well used in the preparation of high-precision current transformers.

[0037] The beneficial technical effects of the present application are as follows: the cobalt-based amorphous soft magnetic material provided in the present application has Co as a basic component, and a small amount of Fe, Mn, Mo, Si and B are added. By controlling the contents of Co, Fe, Mn, Mo, Si and B elements within a specific range, the cobalt-based amorphous constant magnetic permeability core prepared using the cobalt-based amorphous soft magnetic material as a master alloy has different constant magnetic fields, and the magnetic permeability is 2800~3500. At the same time, the cobalt-based amorphous constant magnetic permeability core also has high saturation magnetic field intensity Bs, low loss, and low coercive force, especially has good frequency characteristics and bias characteristics. The bias field characteristics can reach 0-213A / m, the variation is less than 2%, and the coercive force Hc is less than 0.2A / m under direct current, which meets the use requirements of high-precision current transformers. Therefore, it can be well used in the preparation of high-precision current transformers, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the hysteresis loop diagram of the cobalt-based amorphous constant magnetic permeability core prepared in Example 1.

[0039] Figure 2 This is the hysteresis loop diagram of the cobalt-based amorphous constant permeability magnetic core prepared in Example 2. DETAILED DESCRIPTION

[0040] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0041] Example 1: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0042] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is: in atomic percentage, Fe: 3.5%, Mn: 1%, Mo: 3.5%, Si: 12%, B: 6%, Co: balance; wherein the sum of the atomic percentages of Mn and Mo is 4.5%, the sum of the atomic percentages of Si and B is 18%, and the atomic percentage ratio of Si to B is 2:1. Raw materials of cobalt, iron, manganese, molybdenum, silicon, and boron with a purity greater than 99.9% are prepared according to the above elemental composition, and then the raw materials are loaded into a vacuum melting furnace and repeatedly melted 5 times to obtain a master alloy with uniform composition.

[0043] The master alloy is placed in a vacuum single-roll melt rapid quenching equipment and sprayed into an amorphous strip by a single-roll melt rapid quenching method. The linear speed of the cooling roller during the preparation of the amorphous strip is 38m / s, and the thickness of the amorphous strip is 20μm and the width is 5mm. The amorphous strip is wound into a magnetic core with an inner diameter of 4mm, an outer diameter of 8mm and a width of 5mm. The magnetic core is placed in a magnetic heat treatment furnace at room temperature, and under the protection of an inert gas, the temperature is raised to 360°C at a heating rate of 3°C / min. At this temperature and a magnetic field strength of 50kA / m, the temperature is kept for 1 hour for transverse magnetic field heat treatment to obtain a magnetic core after magnetic field heat treatment. The magnetic core after magnetic field heat treatment is cooled to room temperature at a cooling rate of 3°C / min to obtain a cobalt-based amorphous constant magnetic permeability magnetic core.

[0044] The soft magnetic DC tester was used to make a hysteresis loop of the cobalt-based amorphous constant permeability magnetic core, and its soft magnetic properties were tested alkaline. The hysteresis loop diagram was shown in Figure 1 The test results show that the saturation magnetic induction intensity Bs value of the prepared cobalt-based amorphous constant permeability magnetic core is 0.8813T, the coercive force Hc is 0.174A / m, the magnetic permeability (relative magnetic permeability) is 3105, and the magnetic permeability decays <2% at a frequency of 1kHz-100kHz and a bias field of 0~205A / m; at a frequency of 1kHz-1MHz, the magnetic permeability decays ≤5%, and the frequency characteristics are good.

[0045] Example 2: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0046] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is: in atomic percentage, Fe: 3.5%, Mn: 3.2%, Mo: 4.6%, Si: 14%, B: 12.7%, Co: balance; wherein the sum of the atomic percentages of Mn and Mo is 7.8%, the sum of the atomic percentages of Si and B is 26.7%, and the atomic percentage ratio of Si to B is 1.1:1. Raw materials of cobalt, iron, manganese, molybdenum, silicon, and boron with a purity greater than 99.9% are prepared according to the above elemental composition, and then the raw materials are loaded into a vacuum melting furnace and repeatedly melted 5 times to obtain a master alloy with uniform composition.

[0047] The subsequent preparation method is the same as that in Example 1, and a cobalt-based amorphous constant magnetic permeability core is obtained. A soft magnetic DC tester is used to make a hysteresis loop of the cobalt-based amorphous constant magnetic permeability core, and its soft magnetic properties are tested for alkalinity. The hysteresis loop diagram is shown in FIG. Figure 2 The test results show that the saturation magnetic induction intensity Bs value of the prepared cobalt-based amorphous constant permeability magnetic core is 0.9161T, the coercive force Hc is 0.185A / m, the magnetic permeability (relative magnetic permeability) is 2950, ​​and the magnetic permeability decays <2% at a frequency of 1kHz-100kHz and a bias field of 0~196A / m; at a frequency of 1kHz-1MHz, the magnetic permeability decays ≤8%, and the frequency characteristics are good.

[0048] Example 3: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0049] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is: in atomic percentage, Fe: 3.5%, Mn: 2.5%, Mo: 3.5%, Si: 12%, B: 8%, Co: balance; wherein the sum of the atomic percentages of Mn and Mo is 6.0%, the sum of the atomic percentages of Si and B is 20%, and the atomic percentage ratio of Si to B is 1.5:1. Raw materials of cobalt, iron, manganese, molybdenum, silicon, and boron with a purity greater than 99.9% are prepared according to the above elemental composition, and then the raw materials are loaded into a vacuum melting furnace and repeatedly melted 5 times to obtain a master alloy with uniform composition.

[0050] The subsequent preparation method is the same as that in Example 1, and a cobalt-based amorphous constant magnetic permeability core is obtained. A soft magnetic DC tester is used to make a hysteresis loop of the obtained cobalt-based amorphous constant magnetic permeability core, and its soft magnetic properties are alkaline tested. The test results show that the saturation magnetic induction intensity Bs value of the obtained cobalt-based amorphous constant magnetic permeability core is 0.9784T, the coercive force Hc is 0.169A / m, and the magnetic permeability (relative magnetic permeability) is 3450. At a frequency of 1kHz-100kHz and a bias field of 0~213A / m, the magnetic permeability attenuation is <2%; at a frequency of 1kHz-1MHz, the magnetic permeability attenuation is ≤4%, and the frequency characteristics are good.

[0051] Example 4: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0052] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is: in atomic percentage, Fe: 5%, Mn: 2.5%, Mo: 3.5%, Si: 12%, B: 8%, Co: balance; wherein the sum of the atomic percentages of Mn and Mo is 6.0%, the sum of the atomic percentages of Si and B is 20%, and the atomic percentage ratio of Si to B is 1.5:1. Raw materials of cobalt, iron, manganese, molybdenum, silicon, and boron with a purity greater than 99.9% are prepared according to the above elemental composition, and then the raw materials are loaded into a vacuum melting furnace and repeatedly melted 5 times to obtain a master alloy with uniform composition.

[0053] The subsequent preparation method is the same as that in Example 1, and a cobalt-based amorphous constant magnetic permeability core is obtained. A soft magnetic DC tester is used to make a hysteresis loop of the obtained cobalt-based amorphous constant magnetic permeability core, and its soft magnetic properties are alkaline tested. The test results show that the saturation magnetic induction intensity Bs value of the obtained cobalt-based amorphous constant magnetic permeability core is 0.8752T, the coercive force Hc is 0.207A / m, and the magnetic permeability (relative magnetic permeability) is 3150. At a frequency of 1kHz-100kHz and a bias field of 0~192A / m, the magnetic permeability attenuation is <2%; at a frequency of 1kHz-1MHz, the magnetic permeability attenuation is ≤5%, and the frequency characteristics are good.

[0054] Example 5: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0055] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is: in atomic percentage, Fe: 1%, Mn: 2.5%, Mo: 3.5%, Si: 12%, B: 8%, Co: balance; wherein the sum of the atomic percentages of Mn and Mo is 6.0%, the sum of the atomic percentages of Si and B is 20%, and the atomic percentage ratio of Si to B is 1.5:1. Raw materials of cobalt, iron, manganese, molybdenum, silicon, and boron with a purity greater than 99.9% are prepared according to the above elemental composition, and then the raw materials are loaded into a vacuum melting furnace and repeatedly melted 5 times to obtain a master alloy with uniform composition.

[0056] The subsequent preparation method is the same as that in Example 1, and a cobalt-based amorphous constant magnetic permeability core is obtained. A soft magnetic DC tester is used to make a hysteresis loop of the obtained cobalt-based amorphous constant magnetic permeability core, and its soft magnetic properties are alkaline tested. The test results show that the saturation magnetic induction intensity Bs value of the obtained cobalt-based amorphous constant magnetic permeability core is 0.7883T, the coercive force Hc is 0.192A / m, and the magnetic permeability (relative magnetic permeability) is 2800. At a frequency of 1kHz-100kHz and a bias field of 0~172A / m, the magnetic permeability attenuation is <2%; at a frequency of 1kHz-1MHz, the magnetic permeability attenuation is ≤8%, and the frequency characteristics are good.

[0057] Example 6: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0058] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is the same as that in Example 1.

[0059] The master alloy is placed in a vacuum single-roll melt rapid quenching equipment and sprayed into an amorphous strip by a single-roll melt rapid quenching method. The linear speed of the cooling roller during the preparation of the amorphous strip is 30m / s, and the thickness of the amorphous strip is 29μm and the width is 5mm. The amorphous strip is wound into a magnetic core with an inner diameter of 4mm, an outer diameter of 8mm and a width of 5mm. The magnetic core is placed in a magnetic heat treatment furnace at room temperature, and under the protection of an inert gas, the temperature is raised to 360°C at a heating rate of 3°C / min. The magnetic field heat treatment is carried out for 1 hour at this temperature and a magnetic field strength of 50kA / m to obtain a magnetic core after magnetic field heat treatment. The magnetic core after magnetic field heat treatment is cooled to room temperature at a cooling rate of 3°C / min to obtain a cobalt-based amorphous constant magnetic permeability magnetic core.

[0060] The soft magnetic DC tester was used to make a hysteresis loop of the cobalt-based amorphous constant permeability magnetic core, and its soft magnetic properties were tested alkaline. The test results show that the saturation magnetic induction intensity Bs value of the cobalt-based amorphous constant permeability magnetic core is 0.7592T, the coercive force Hc is 0.229A / m, the magnetic permeability (relative magnetic permeability) is 2700, and the magnetic permeability decay is less than 4% at a frequency of 1kHz-100kHz and a bias field of 0~150A / m; at a frequency of 1kHz-1MHz, the magnetic permeability decay is ≤10%, and the frequency characteristics are good.

[0061] Example 7: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0062] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is the same as that in Example 1.

[0063] The master alloy is placed in a vacuum single-roll melt rapid quenching equipment and sprayed into an amorphous strip by a single-roll melt rapid quenching method. The linear speed of the cooling roller during the preparation of the amorphous strip is 38m / s, and the thickness of the amorphous strip is 20μm and the width is 5mm. The amorphous strip is wound into a magnetic core with an inner diameter of 4mm, an outer diameter of 8mm and a width of 5mm. The magnetic core is placed in a magnetic heat treatment furnace at room temperature, and under the protection of an inert gas, the temperature is raised to 400℃ at a heating rate of 3℃ / min. The magnetic field heat treatment is carried out for 1 hour at this temperature and a magnetic field strength of 100kA / m to obtain a magnetic core after magnetic field heat treatment. The magnetic core after magnetic field heat treatment is cooled to room temperature at a cooling rate of 3℃ / min to obtain a cobalt-based amorphous constant magnetic permeability magnetic core.

[0064] The soft magnetic DC tester was used to make a hysteresis loop of the cobalt-based amorphous constant permeability magnetic core, and its soft magnetic properties were tested alkaline. The test results show that the saturation magnetic induction intensity Bs value of the cobalt-based amorphous constant permeability magnetic core is 0.8013T, the coercive force Hc is 0.194A / m, the magnetic permeability (relative magnetic permeability) is 2900, and the magnetic permeability decays <2% at a frequency of 1kHz-100kHz and a bias field of 0~182A / m; at a frequency of 1kHz-1MHz, the magnetic permeability decays ≤8%, and the frequency characteristics are good.

[0065] Example 8: Preparation of Cobalt-based Amorphous Constant Permeability Magnetic Core

[0066] Preparation of master alloy: The composition of the cobalt-based amorphous soft magnetic material used in the master alloy is the same as that in Example 1.

[0067] The master alloy is placed in a vacuum single-roll melt rapid quenching equipment and sprayed into an amorphous strip by a single-roll melt rapid quenching method. The linear speed of the cooling roller during the preparation of the amorphous strip is 38m / s, and the thickness of the amorphous strip is 20μm and the width is 5mm. The amorphous strip is wound into a magnetic core with an inner diameter of 4mm, an outer diameter of 8mm and a width of 5mm. The magnetic core is placed in a magnetic heat treatment furnace at room temperature, and under the protection of an inert gas, the temperature is raised to 300℃ at a heating rate of 3℃ / min. The magnetic field heat treatment is carried out for 1 hour at this temperature and a magnetic field strength of 20kA / m to obtain a magnetic core after magnetic field heat treatment. The magnetic core after magnetic field heat treatment is cooled to room temperature at a cooling rate of 3℃ / min to obtain a cobalt-based amorphous constant magnetic permeability magnetic core.

[0068] The soft magnetic DC tester was used to make a hysteresis loop of the cobalt-based amorphous constant permeability magnetic core, and its soft magnetic properties were tested alkaline. The test results show that the saturation magnetic induction intensity Bs value of the cobalt-based amorphous constant permeability magnetic core is 0.7921T, the coercive force Hc is 0.200A / m, the magnetic permeability (relative magnetic permeability) is 2800, and the magnetic permeability decays <2% at a frequency of 1kHz-100kHz and a bias field of 0~193A / m; at a frequency of 1kHz-1MHz, the magnetic permeability decays ≤8%, and the frequency characteristics are good.

[0069] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A cobalt-based amorphous constant magnetic core, characterized in that: The master alloy used in the preparation process of the constant magnetic permeability magnetic core is a cobalt-based amorphous soft magnetic material; In terms of atomic percentage, the soft magnetic material is composed of the following elements: Fe: 3-3.5%, Mn: 1-6%, Mo: 3-6%, Si: 10-20%, B: 5-20%, and Co: the balance; and the sum of the atomic percentage contents of Mn and Mo is 4-8%; the sum of the atomic percentage contents of Si and B is 18-24%, and the ratio of the atomic percentage contents of Si to B is (1.5-2):1; The method for preparing the cobalt-based amorphous constant magnetic permeability core comprises the following steps: S1, spraying the master alloy into an amorphous strip by a single-roll melt rapid quenching method, and then winding the amorphous strip into a magnetic core; S2, performing magnetic field heat treatment on the magnetic core under inert gas protection or vacuum conditions to obtain a magnetic core after magnetic field heat treatment; S3, cooling the magnetic core after the magnetic field heat treatment to room temperature to obtain the cobalt-based amorphous constant magnetic permeability magnetic core; In step S2, the heating rate during the magnetic field heat treatment is 1-10°C / min, the holding temperature is 300-400°C, and the holding time is 0.5-5 hours; the magnetic field intensity during the magnetic field heat treatment is 10-100 kA / m; In step S3, the cooling rate is 3-10°C / min.

2. A method for preparing a cobalt-based amorphous constant magnetic permeability core as claimed in claim 1, characterized in that: The method comprises the following steps: S1, spraying the master alloy into an amorphous strip by a single-roll melt rapid quenching method, and then winding the amorphous strip into a magnetic core; S2, performing magnetic field heat treatment on the magnetic core under inert gas protection or vacuum conditions to obtain a magnetic core after magnetic field heat treatment; S3, cooling the magnetic core after the magnetic field heat treatment to room temperature to obtain the cobalt-based amorphous constant magnetic permeability magnetic core; In step S2, the heating rate during the magnetic field heat treatment is 1-10°C / min, the holding temperature is 300-400°C, and the holding time is 0.5-5 hours; the magnetic field intensity during the magnetic field heat treatment is 10-100 kA / m; In step S3, the cooling rate is 3-10°C / min.

3. The method according to claim 2, characterized in that In step S1, the linear speed of the cooling roller during the preparation of the amorphous strip is 35-40 m / s, and the thickness of the prepared amorphous strip is 16-24 μm and the width is 5-30 mm.

4. Use of the cobalt-based amorphous constant magnetic permeability core as claimed in claim 1 or the cobalt-based amorphous constant magnetic permeability core prepared by the method as claimed in claim 2 or 3 in the preparation of a high-precision current transformer.

Citation Information

Patent Citations

  • Amorphous transformer for power distribution

    CN108109803A

  • High-squareness cobalt-based amorphous alloy iron core and preparation method thereof

    CN110400670A